The unfavorable lipid environment reduced caveolin-1 expression in apical membranes from human preeclamptic placentas - Levi, L. (2016)
Syncytialization process is associated with a reduction in the number of caveolas, and a decreased of caveolin-1 (Cav-1). Differentiation of syncytiotrophoblast affects the membranes phospholipid composition. Thus, disturbances in these processes are related to pathological conditions such as preeclampsia. Objective To analyse the lipid composition of the apical (MVM) and the basal (BM) membranes of syncytiotrophoblast and its relationship with Cav-1 expression in normal and preeclamptic placentas. Molecular expression of Cav-1 was determined in MVM and BM from normal and preeclamptic placentas and in detergent-resistant membranes (DRMs). Phospholipids were analyzed by thin layer chromatography. Cholesterol was also determined by enzymatic assay. Membrane fluidity was evaluated by electron paramagnetic resonance. Sphingomyelin (SM) molecular species were analyzed and quantified by gas-liquid chromatography and mass spectrometry. Cav-1 was significantly reduced in MVM from preeclamptic placentas. Regarding Cav-1 localization, it was barely detectable in syncytiotrophoblast but it was present in the endothelium. Western blots also showed a significantly decrease of Cav-1 in the apical DRMs from preeclamptic placentas. Lipid analysis showed an increase SM in MVM from preeclamptic placentas without changes in cholesterol. Preeclamptic MVM fluidity decreased significantly and we found an increase in C18:1 fatty acids of SM. We concluded that preeclamptic-MVMs are more rigid than normal ones, possible due to an increment on SM. Moreover, the increase of long and unsaturated SM molecular specie found in these vesicles may disrupt the ability of SM to assemble into lipid rafts in the luminal leaflet of the bilayer, creating an unfavorable environment for Cav-1.